Estratégias participativas construídas entre estudantes e professora nas aulas de Educação Física - Baio, Cristina Gil de Carvalho (Universidade Federal de São Carlos, 2023)
On behalf of pandemic and social isolation we have been through, there was a potentiation of a new global reality, since the population was restricted to their homes and, in many cases, the systematized body practices were left out. Within the school context where I work, I could observe such situation, because most of the students took the Physical Education class as the only time in wich they could perform oriented body practices. Towards that scenario of returning to the presential classes, the objective of the study is analyse the implications of a teaching process to the construtction of knowledge related to the experimentation of body practices through integrated strategies in Physical Education classes.The project is based on a qualitative research approach, characterized by research-action, in wich the professor-researcher, planned and taught the pedagogical activities. The sudy was performed during one school year, involving 26 students from a 4° grade class of the elementary school, from a municipal school located inner-state São Paulo. The data were collected through class diaries developed by the professor-researcher, rounds of conversation and a mixed questionnaire with open and closed questions applied to the students. After collection, the data were qualitatively analyzed through the establishment of two categories, namely: 1 – The construction of students’ knolwedge from the paticipatory process, wich allowed us to analyse the construction process of the students’ knowledge, within the context of the Physical Education classes in the face of the content provided; and, 2 – Possibilities and challenges in the implementation of the participatory planning proposal, in wich we seek to promote means of recognition of the problems, the exaltation of achievements and over this analyse and reflect on possible solutions, so as not to be only on complaints and we can make announcements. Thus we conclude, in general, the dynamics of the developd planning through participative strategies were very real allowing the corresponsibility of the students in teaching and learning process and the valuation of their knowledge, breaking the traditionally logic establiched to the school education, in other words, viewing the students as the ones who learn and the professors the ones who teach.
Participatory strategies built between students and teacher in Physical Education classes
Keywords: Educação física escolar; Planejamento participativo; Experimentação; Vivências de práticas corporais; CIENCIAS DA SAUDE::EDUCACAO FISICA